Numerical Simulation of an Air-Core Vortex and Its Suppression at an Intake Using OpenFOAM - Domfeh, Martin Kyereh; Gyamf, Samuel; Amo-Boateng, Mark (Fluids, 2020)
: A common challenge faced by engineers in the hydraulic industry is the formation of free surface vortices at pump and power intakes. This undesirable phenomenon which sometimes entrains air could result in several operational problems: noise, vibration, cavitation, surging, structural damage to turbines and pumps, energy losses, efficiency losses, etc. This paper investigates the numerical simulation of an experimentally observed air-core vortex at an intake using the LTSInterFoam solver in OpenFOAM. The solver uses local time-stepping integration. In simulating the air-core vortex, the standard k − ε, realizable k − ε, renormalization group (RNG) k − ε and the shear stress transport (SST) k − ω models were used. The free surface was modelled using the volume of fluid (VOF) model. The simulation was validated using a set of analytical models and experimental data. The SST k − ω model provided the best results compared to the other turbulence models. The study was extended to simulate the effect of installing an anti-vortex device on the formation of a free surface vortex. The LTSInterFoam solver proved to be a reliable solver for the steady state simulation of a free surface vortex in OpenFOAM
Keywords: intake; air-core vortex; LTSInterFoam; OpenFOAM; volume of fluid (VOF); Robert Andoh; Eric Antwi Ofosu; ACE: Energy and Environmental Sustainability